THE ROLE OF TISSUE OXYMETRY AND DIGITAL DYNAMOMETRY IN THE PREVENTION OF INTERSPINOUS FIXATORS INSTABILITY - Chertkov Kuzma Alexandrovich (Journal of Global Pharma Technology, 2016)
The work describes the results of intraoperative tissue optical oxymetry when implanting interspinous fixators in 17 patients with instability in the lumbar spinal segments with the use of a dynamometric digital device. The aim of the study was to develop preventive measures against vascularization disorders in the bone structures as a basic condition for successful osseointegration. The parameters of safe compression (25-27 N/m) of interspinous processes with fixation devices when implanting stabilizing fixators were determined in the course of the study. Keywords: Instability, Tissue optical oxymetry, Implants, Digital dynamometry, Spinal motor segment